Undrained shear behavior of mixed mine waste rock and tailings - Hamade, Matteus M. P., author; Bareither, Christopher A., advisor; Scalia, Joseph, IV, committee member; Magloughlin, Jerry F., committee member (Colorado State University. Libraries, 2017)
The objective of this study was to evaluate the effect of variability in mixture ratio (R) and tailings composition on shear behavior and shear strength of mixed mine waste rock and tailings (WR&T). Crushed gravel was used as a synthetic waste rock (SWR), and mixtures of sand, silt, and clay were used to create two synthetic mine tailings: average synthetic tailings (AST) and fine synthetic tailings (FST). Mixtures of WR&T were prepared with varying R to represent coarse-dominated structures to fine-dominated structures, as well as R = Ropt, which represents an optimal mixture ratio where tailings "just fill" void space of the waste rock. Pure SWR, pure tailings, and WR&T mixtures containing AST and FST were tested in consolidated-undrained triaxial compression at target effective confining stresses (σʹc) of 10, 50, and 100 kPa. The SWR and WR&T triaxial specimens were 150 mm in diameter by 300 mm tall, whereas the AST and FST specimens were 38 mm in diameter by 76 mm tall. Dilative, strain-hardening behavior was observed for all triaxial tests on pure SWR, whereas contractive, strain-softening behavior was observed for all triaxial tests on pure FST. Triaxial tests on pure AST exhibited both dilative, strain-hardening behavior and contractive, strain-softening behavior; contractive behavior was observed for AST specimens that contained larger initial void ratios (e) after consolidation. Waste rock and tailings mixtures that had coarse- dominated structures exhibited comparable undrained shear behavior to pure SWR. Fine- dominated WR&T mixtures exhibited undrained shear behavior that was more similar to the pure tailings; however, the addition of waste rock to tailings was observed to mitigate some contractive behavior as the addition of waste rock to tailings increased the tendency of the WR&T mixtures to exhibit dilative response. Mixtures prepared to target Ropt exhibited dilative, strain-hardening behavior. An analysis of flow behavior indicated that the addition of waste rock to tailings to create WR&T mixtures improved flow behavior of pure tailings to a limited- or no- flow behavior that improves resistance against static liquefaction. Shear strength parameters for all materials were calculated based on stress paths in p'-q space reaching the failure line (Kf Line). Pure materials yielded effective tangent friction angle (φ't) of 38° for AST, 39° for FST, and 41° for SWR. The AST mixture with R ≈ Ropt yielded φ't = 48°, which was the largest φ't of all mixtures. Fine-dominated structures of AST (i.e., R < Ropt) yielded φ't = 44°. This increase in φ't relative to the pure AST was attributed to the additional frictional resistance between the silty-sand AST and the SWR. The FST WR&T mixtures were only fine-dominated structures as all specimens yielded R < Ropt. The effective stress friction angle increased from 32° for FST mixtures prepared at R = 1.7 to 38° for R = 2.5. The lower φ't for the FST mixtures relative to the pure FST was attributed to looser tailings (i.e., higher void ratio) compared to the pure tailings specimens. A steady-state analysis was performed with the assistance of mixture theory to determine if a single steady state line (SSL) could be relevant for WR&T mixtures that was independent of mixture ratio. Results showed that the use of equivalent void ratios for the steady-state analysis of mixtures provide a reasonable prediction of undrained shear behavior of mixtures. The analysis on AST mixtures demonstrates the effectiveness of equivalent void ratios both for fine- and coarse-dominated structures. The FST mixtures also supports the effectiveness of fine-dominated equivalent void ratios for assessing undrained shear behavior of mixtures. The steady state analysis supports the use of a single SSL for mixtures based on pure tailings and the use of equivalent void ratios that are both independent of R.
Keywords: mine waste; triaxial test; shear behavior; geoenvironmental